(untitled) (Journal of Biomedical Investigation, 2008)
The present study was designed to assess the prevalence of hypertension, awareness and control on a group of women attending an annual meeting in the South Eastern Nigeria popularly called ’August’ meeting. A total 164 women (mean age: 54.4 ± 12.7 yrs.) attending ’August’ meeting had their BP measured and history of hypertension and/ or history of anti-hypertensive drug use taken. Hypertension was defined as systolic blood pressure ≥ 140mmHg and diastolic blood pressure ≥ 90mmHg. The prevalence of hypertension was 44.5% while 43.7% were aware they were hypertensive. 90.3% of those aware of being hypertensive were on anti-hypertensive drugs of which 13% had BP ≤ 140/90mmHg. There is a high prevalence of hypertension in our women and efforts should be made to ensure that their blood pressure is well controlled.